Dynamics of SARS-CoV2 Infection and Multi-Drug Resistant Bacteria Superinfection in Patients With Assisted Mechanical Ventilation - Mazzariol, Annarita; Benini, Anna; Unali, Ilaria; Nocini, Riccardo; Smania, Marcello; Bertoncelli, Anna; De Sanctis, Francesco; Ugel, Stefano; Donadello, Katia; Polati, Enrico; Gibellini, Davide (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: To investigate the presence of bacteria and fungi in bronchial aspirate (BA) samples from 43 mechanically ventilated patients with severe COVID-19 disease. Methods: Detection of SARS-CoV-2 was performed using Allplex 2019-nCoV assay kits Isolation and characterisation of bacteria and fungi were carried out in BA specimens treated with 1X dithiothreitol 1% for 30 min at room temperature, using standard culture procedures. Results: Bacterial and/or fungal superinfection was detected in 25 out of 43 mechanically ventilated patients, generally after seven days of hospitalisation in an intensive care unit (ICU). Microbial colonisation (Colonies Forming Units (CFU) <1000 colonies/ml) in BA samples was observed in 11 out of 43 patients, whereas only seven patients did not show any signs of bacterial or fungal growth. Pseudomonas aeruginosa was identified in 17 patients. Interestingly, 11 out of these 17 isolates also showed carbapenem resistance. The molecular analysis demonstrated that resistance to carbapenems was primarily related to OprD mutation or deletion. Klebsiella pneumoniae was the second most isolated pathogen found in 13 samples, of which eight were carbapenemase-producer strains. Conclusion: These data demonstrate the detection of bacterial superinfection and antimicrobial resistance in severe SARS-CoV-2-infected patients and suggest that bacteria may play an important role in COVID-19 evolution. A prospective study is needed to verify the incidence of bacterial and fungal infections and their influence on the health outcomes of COVID-19 patients.